COVID-19 and Type 1 Diabetes: Concerns and Challenges: COVID19 and T1D - Iughetti, Lorenzo; Trevisani, Viola; Cattini, Umberto; Bruzzi, Patrizia; Lucaccioni, Laura; Madeo, Simona; Predieri, Barbara (Acta Biomedica Atenei Parmensis, 2020)
Due to the current COVID-19 pandemic, worldwide population’s lifestyle has changed dramatically, causing psychosocial consequences.  Patients presenting a preexisting chronic condition, as Type 1 Diabetes (T1D), are the ones suffering the most from this situation. Moreover, people affected by diabetes are the ones with the worst prognosis, if infected by SARS-CoV-2.  We analyzed why patients with T1D were poorly represented between the subjects hospitalized for COVID-19 and why the cases of diabetic ketoacidosis (DKA) were fewer and more severe compared with the past years. Furthermore, literature has showed how patients of all ages with T1D did not experience a deterioration in their glucose control throughout the lockdown. Among other causes, this is also due to the surging use of telemedicine. Finally, we tried to understand how the coronavirus tropism for endocrine tissues could influence the future epidemiology of T1D, focusing on the effects they have on pancreatic β-cells.